2011
DOI: 10.1038/cdd.2011.91
|View full text |Cite
|
Sign up to set email alerts
|

BID regulates AIF-mediated caspase-independent necroptosis by promoting BAX activation

Abstract: Alkylating DNA-damage agents such as N-methyl-N 0 -nitro-N 0 -nitrosoguanidine (MNNG) trigger necroptosis, a newly defined form of programmed cell death (PCD) managed by receptor interacting protein kinases. This caspase-independent mode of cell death involves the sequential activation of poly(ADP-ribose) polymerase-1 (PARP-1), calpains, BAX and AIF, which redistributes from mitochondria to the nucleus to promote chromatinolysis. We have previously demonstrated that the BAX-mediated mitochondrial release of AI… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
88
0

Year Published

2012
2012
2016
2016

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 111 publications
(93 citation statements)
references
References 40 publications
5
88
0
Order By: Relevance
“…A limited extent or duration of elevated Ca 2 + may not result in the extent of bioenergetic impairment necessary for evoking acute cell death but can promote caspaseindependent apoptosis through calpain-mediated mitochondrial release of apoptosis inducing factor (AIF) (Polster et al, 2005). Calpains can also cleave inactive BH3 domain-only proteins, forming active peptides, e.g., truncated Bid (tBid), which bind to proapoptotic and antiapoptotic proteins, e.g., Bax and Bcl2, resulting in outer membrane permeabilization and release of cytochrome c, AIF, and other proteins that trigger either caspase-dependent or caspase-independent programmed cell death (Krajewska et al, 2004;Cabon et al, 2012). A greater mitochondrial insult, which leads to delayed neuronal Ca 2 + deregulation, is more apt to induce rapid necrosis, particularly when PTP opening causes irreversible mitochondrial inner membrane depolarization and osmotic mitochondrial lysis (Pivovarova and Andrews, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…A limited extent or duration of elevated Ca 2 + may not result in the extent of bioenergetic impairment necessary for evoking acute cell death but can promote caspaseindependent apoptosis through calpain-mediated mitochondrial release of apoptosis inducing factor (AIF) (Polster et al, 2005). Calpains can also cleave inactive BH3 domain-only proteins, forming active peptides, e.g., truncated Bid (tBid), which bind to proapoptotic and antiapoptotic proteins, e.g., Bax and Bcl2, resulting in outer membrane permeabilization and release of cytochrome c, AIF, and other proteins that trigger either caspase-dependent or caspase-independent programmed cell death (Krajewska et al, 2004;Cabon et al, 2012). A greater mitochondrial insult, which leads to delayed neuronal Ca 2 + deregulation, is more apt to induce rapid necrosis, particularly when PTP opening causes irreversible mitochondrial inner membrane depolarization and osmotic mitochondrial lysis (Pivovarova and Andrews, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Bax was also found to be indispensable for AIF-mediated cell death. 13,14) On the contrary, the antiapoptotic molecules such as Bcl-2 and Bcl-xL can be activated to prevent the conformational change and oligomerization of Bax and Bak. 44,45) In this study, we found cordycepol C could induce the disruption of Δψ m and the translocation of Bax from cytoplasm to mitochondria (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…8,12,13,16,45,46) AIF can induce chromatin condensation and cleavage of DNA into high molecular weight fragments (50-300 kb), while endonuclease G can produce oligonucleosomal DNA fragments. 8,16) Our results revealed that cordycepol C induced the release of AIF and Endo G from the mitochondria and their translocation to the nucleus in a time-dependent manner (Fig.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…2) (Patterson et al 2000;Wabnitz et al 2010;Lee et al 2010). The key regulators of caspase-independent apoptosis are located on the mitochondria membranes, whose integrity (mitochondrial outer membrane permeabilization (MOMP)) is regulated by multiple proteins and processes, including Bcl-2 family members (Esposti 2010), BH3-only proteins (Cabon et al 2012), tumor suppressor protein P53 (Galluzzi et al 2008a;Galluzzi et al 2011), Protein kinase Cs (AllenPetersen et al 2010;Paoletti et al 2010), epigenetic perturbations (Yelamanchili et al 2010;Tenedini et al 2010;Sancho-Pelluz et al 2010;Lei et al 2010;Lanzillotta et al 2010), and cell cycle perturbations ( Fig. 2) (Mitchell et al 2010).…”
Section: Apoptosis -The Programmed Cell Deathmentioning
confidence: 99%